Pengetahuan dan Persepsi Ibu Hamil tentang Akupressur dalam Mengatasi Ketidaknyamanan pada Kehamilan - Nurbaiti, Nurbaiti; Tiwi, Laida Sanilpa (Universitas Baiturrahim, 2024)
Pregnancy is a natural and physiological process, along with the increasing age of pregnancy, psychological and physiological changes will be experienced by the pregnant mother with these changes, then there are some discomforts experienced by the pregnant mother such as the mother will feel nausea and vomiting in the first trimester, back pain , feeling tired, back pain and mood changes, there are many ways that pregnant women can do when facing discomfort during pregnancy with either pharmacological or non-pharmacological therapy. Acupressure is a non-pharmacological therapy where the technique in this therapy uses fingers that are done on the same points as used in acupuncture therapy, the benefits of acupressure therapy can reduce discomfort during pregnancy. This research aims to find out the knowledge and perception of pregnant women about acupressure in overcoming discomfort during pregnancy, this research uses a designdescriptive, which was carried out at PMB Rosmala Aini, the population in this study were all pregnant women who visited PMB Rosmala Aini, totaling 25 pregnant women, the sample was taken using the total sampling technique, when the research was carried out in October 2022-August 2023 the results of this study averaged the average age of the mother is 26.76 with the lowest age being 21 years and the highest being 37 years, the majority of the work of housewives is 20 (80%), high school education is 23 (92%) and good knowledge is 22 (88%), and the perception of pregnant women towards acupressure 23 (92%) mothers have a positive perception. Acupressure can be used as an alternative as a non-pharmacological method in dealing with discomfort in pregnant women so that mothers can do it independently at home.